Proteinase-Activated Receptors of Digestive Systems - G. F. Korotko (Медицинский вестник Юга России, 2012)
The enzymes exosecreted by digestive glands, especially proteinases have not only digestive but signal role. The role is realized by means of regulatory peptide formation, stimulation and inhibition of their release, stimulation of special proteinase-activated receptors of digestive organs and adaptation their digestive and protective function. The enzymes endo-secreted by digestive glands have the same role. The examples of complex enzyme regulation of digestive and non-digestive organ functions in normal and pathologic condition were demonstrated.